Transformações nas condições de trabalho e de vida em comunidades tradicionais no Maranhão no contexto do desenvolvimento desigual e combinado capitalista, pós 1970 - ARCANGELI, Saulo Costa (2024)
In this thesis I present the results of in-depth studies on the object configured by the transformations that occurred in working and living conditions in traditional communities in Maranhão, in the context of the installation of large capitalist enterprises focused, primarily, on the export of commodities (minerals, cellulose, gold and agribusiness). A developmental option by governments in Maranhão, since the 1970s, which is at the service of large national and transnational corporations and generates perverse implications in traditional communities in Maranhão, especially São Luís, in the context of uneven and combined capitalist development. The state of Maranhão enters the modern industrial era and technological advances without solving essential problems (transport, water and basic sanitation, work, education, food security, health) and without the legitimate and legal guarantee of protection to territories, causing social implications, political and economic issues in the state of Maranhão. A fundamental process to meet the external needs of capitalism and its transnational companies, even if to do so they attack several communities that disappear or are forced to “adapt” to the leaps in capitalist development that destroy nature, forms of production based on extractivism and in small farming, their traditional cultures and their own lives.I reinforce the opposition to this option of capital, in organic alliance with the State, based on the intervention of workers, socio-political supporters, union, popular and party movement organizations, in the struggles waged by traditional communities in confronting large enterprises and need for a struggle in opposition to the capitalist mode of production, with a view to advancing towards socialist society. The method used is historical and dialectical materialist, as it is the best way to extract from the object analyzed here, its multiple determinations, based on the real movement of traditional communities in the rural area of São Luís and municipalities in the state of Maranhão. The theoretical-methodological body of this method gives meaning and direction to the technical-scientific instruments used both in the investigation and in the analysis of the results presented in this thesis.